2014
DOI: 10.1177/0192623314556516
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pathobiology of Environmentally Induced Lung Cancers in Humans and Rodents

Abstract: Lung cancer is the number one cause of cancer-related deaths in humans worldwide. Environmental factors play an important role in the epidemiology of these cancers. Rodents are the most common experimental model to study human lung cancers and are frequently used in bioassays to identify environmental exposure hazards associated with lung cancer. Lung tumors in rodents are common, particularly in certain strains of mice. Rodent lung tumors are predominantly bronchioloalveolar carcinomas and usually follow a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 58 publications
(82 reference statements)
0
14
0
Order By: Relevance
“…The finding of significantly increased focal adenomatous alveolar hyperplastic lesions in mice (male, B6C3F1) following inhalation of MWCNT-7 (Sargent et al 2014) provides evidence of pre-neoplastic changes similar to those observed in humans that have the potential to progress to bronchiolo-alveolar carcinoma or adenocarcinoma (Brambilla et al 2001; Pandiri 2015). Presently, the mechanism of the cell proliferation is not known.…”
Section: Discussion Of Review Findingsmentioning
confidence: 85%
See 3 more Smart Citations
“…The finding of significantly increased focal adenomatous alveolar hyperplastic lesions in mice (male, B6C3F1) following inhalation of MWCNT-7 (Sargent et al 2014) provides evidence of pre-neoplastic changes similar to those observed in humans that have the potential to progress to bronchiolo-alveolar carcinoma or adenocarcinoma (Brambilla et al 2001; Pandiri 2015). Presently, the mechanism of the cell proliferation is not known.…”
Section: Discussion Of Review Findingsmentioning
confidence: 85%
“…Such studies are needed to improve the mechanistic evidence for assessing the potential carcinogenicity of CNT and CNF, since it is not feasible to perform chronic rodent bioassays of each material. The focal adenomatous hyperplasia observed in alveolar epithelial tissues in mice exposed to MWCNT-7 (Sargent et al 2014) is considered to resemble the preneoplastic lesion AAH in humans (Section “Epithelial cell proliferation and hyperplasia—MWCNT”) (Brambilla et al 2001; Pandiri 2015). It would be useful to investigate any influence of the physico-chemical properties of the material on the dose–response relationships for pre-neoplastic lesions.…”
Section: Discussion Of Review Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alveolar/bronchiolar adenomas/carcinomas that arise either spontaneously or from chronic chemical exposure are morphologically similar to the adenocarcinoma subtype of the non-small cell lung cancer (NSCLC) in humans (Hong et al , 2008, Pandiri, 2015, Tuveson and Jacks, 1999). Spontaneous lung (SL) tumor (alveolar/bronchiolar carcinomas) incidence in the B6C3F1/N mouse strain ranges from 9.5% (female) – 27.7% (male) (all routes, all vehicles, NTP historical control database 2013), and the incidence of lung tumors after exposure to certain chemicals was considerably higher in chronic NTP bioassays (NTP, 2013a).…”
Section: Introductionmentioning
confidence: 99%